Do exotic salmonids feed on native fauna after escaping from aquaculture cages in Tasmania, Australia? - Abrantes, Kátya Gisela; Lyle, Jeremy Martin; Nichols, Peter D.; Semmens, Jayson Mark (Canadian Journal of Fisheries and Aquatic Sciences, 2011)
Atlantic salmon, Salmo salar , and rainbow trout, Oncorhynchus mykiss , are farmed in Tasmania, Australia, where fish sometimes escape into the natural environment. If escapees are able to survive and feed on native fauna, it is likely that they will have ecosystem impacts. Stomach content, body condition (muscle lipid content and Fulton’ K), stable isotope, and fatty acid analysis were used to determine if escaped salmonids feed on native fauna. Results indicate that, in general, escaped salmonids do not feed on native fauna. Salmonids loose condition after escaping, and escapee stomachs were mostly empty or contained non-nutritious material or feed pellets. Nevertheless, almost a quarter of rainbow trout stomachs contained native fauna. The majority of escapees had biochemical composition similar to caged animals, indicating that these fish had not switched to feed on local food sources. However, a small fraction of escapees conclusively showed changes in biochemical parameters indicative of a shift to feeding on native fauna. Given the numbers and frequency of escapes, this can have an important impact on native species and on the ecology of Macquarie Harbour.